Health-Related Quality of Life and Associated Factors Among Oldest-Old in China - Chen, C. (J Nutr Health Aging, 2020)
OBJECTIVES: The oldest old population has become the fastest growing segment with excess need of care and social support, it is crucial to improve the health-related quality of life (HRQoL) of these populations. This study seeks to evaluate the health status and to investigate modifiable factors associated with health-related quality of life for oldest old adults in China. DESIGN: A cross-sectional population-based study. SETTING: Hainan Province in the south of China. PARTICIPANTS: 1,278 adults aged 80 years or older. METHODS: HRQoL was assessed by three-level EuroQol-5D scale (EQ-5D-3L) and a visual analogue scale (VAS). Demographic and health-related variables were analysed by estimating mean values and standard deviations for continuous variables, percentages and standard deviations for categorical variables. Tobit regressions, ordinary least Squared (OLS) regressions and ordered probit regressions were adopted to determine the associated factors for overall HRQoL and for each health dimension. RESULTS: Anxiety/depression was the least reported problem while mobility was the most frequently reported with problem. Female respondents had lower EQ-5D score (0.76 vs. 0.86) and VAS score (66.55 vs. 69.84) than male respondents. Better health-related quality of life was significantly associated with higher BMI, no drinking habit, more leisure activities, living with family members, good sleeping quality, closer social and family connections, fewer numbers of drugs consumed per day, without having hearing or visual impairment, and fewer chronic conditions, after controlling for potential confounders. CONCLUSION: Findings from this study suggested that quality of life was not only associated with age-related diseases, but also correlated with a range of health-related lifestyles, and factors indicating social and family support. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s12603-020-1327-2 and is accessible for authorized users.